2019
DOI: 10.1016/j.psychres.2018.12.096
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of biofeedback approaches for obsessive-compulsive and related disorders: A systematic review and meta-analysis

Abstract: A B S T R A C TBiofeedback is applied to target excessive and/or deficient physiological signals to help patients identifying and self-managing their symptoms. Biofeedback has been employed in psychiatric disorders, including obsessivecompulsive disorder (OCD), mainly by using neural signals -neurofeedback. Recently, OCD has been integrated into the obsessive-compulsive and related disorders (OCD&RD) category (body dysmorphic, hoarding, trichotillomania/hair-pulling, and excoriation/skin-picking disorders). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 50 publications
(99 reference statements)
0
11
0
Order By: Relevance
“…Meta‐analyses completed by Ferreira et al. (2019), Moore (2000), Reiter et al. (2016), Schoenberg and David (2014), and Steingrimsson et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meta‐analyses completed by Ferreira et al. (2019), Moore (2000), Reiter et al. (2016), Schoenberg and David (2014), and Steingrimsson et al.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, articles included in the ISNR Comprehensive Bibliography (2021) and those that were reported in previously conducted meta-analyses with a similar scope were mined and analyzed for appropriateness of the scope of the present meta-analysis. Meta-analyses completed by Ferreira et al (2019), Moore (2000), Reiter et al (2016), Schoenberg and David (2014), and Steingrimsson et al (2020) were mined for additional articles that could have been missed in our search procedures. Forward citation was not used based on the number of databases, repositories, journal-specific searches, and references mined.…”
Section: Information Sourcesmentioning
confidence: 99%
“…Electroencephalography (EEG) -based NFB is a biofeedback protocol in which information about the participant's brain oscillation patterns is fed back via auditory and/or visual cues in real time operant conditioning is then used to modify these brain oscillations (Niv, 2013;Sitaram et al, 2017;Thatcher, 1998). NFB has been shown to improve function in a variety of behavioral, psychiatric (Schoenberg & David, 2014) and neurological conditions, including depression (Dias & van Deusen, 2011;Fernández-Alvarez et al, 2020;White et al, 2017), anxiety (Hammond, 2005), traumatic brain injury (Thornton & Carmody, 2009), chronic pain (Patel et al, 2020), post-traumatic stress disorder (Steingrimsson et al, 2020), obsessive compulsive disorder (Ferreira et al, 2019), epilepsy (Egner & Sterman, 2006), and attention-deficit/hyperactivity disorder (ADHD) ( (Arns et al, 2009;Bussalb et al, 2019;Groeneveld et al, 2019;Lubar et al, 1995;Micoulaud-Franchi et al, 2014;Pigott & Cannon, 2014;Riesco-Matías et al, 2019;Van Doren et al, 2018), but see (Cortese et al, 2016;Sonuga-Barke et al, 2013)). It has also been shown to improve cognitive performance in healthy individuals (Dessy et al, 2017;Gruzelier, 2014;Reiner et al, 2014;Rozengurt et al, 2016).…”
Section: Promising Non-pharmaceutical Treatment Strategies: Addressinmentioning
confidence: 99%
“…During a neurofeedback session, participants are trained to achieve volitional control of their neural activity through real-time feedback ( Sitaram et al, 2017 ). Potential applications of this approach in psychiatry include the treatment of mood and anxiety disorders, such as depression ( Trambaiolli et al, 2021a ) and obsessive-compulsive disorder (OCD) ( Ferreira et al, 2019 ). Clinical benefits have been reported to persist for weeks or months after training ( Rance et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, targeted functional connectivity has been explored as a potential predictor of neurofeedback training performance. This has been motivated by findings showing that individual differences in resting-state functional connectivity can identify individuals from a large group (Finn et al, 2015), and influence task performances in different cognitive domains (Shen et al, 2017). For example, Scheinost et al (2014) showed that fMRI-based whole-brain functional connectivity could be used as a predictor of affective neurofeedback treatment success in patients with OCD (Scheinost et al, 2014).…”
Section: Introductionmentioning
confidence: 99%